(untitled) (Bangladesh Journal of Animal Science, 2019)
Supplementation of concentrate feed during late pregnancy of doe is an approach to improve milk yield and kid performance after kidding. The experiment was conducted to find out appropriate level and duration of supplementation to the pregnant doe. The data of the experiment were analyzed applying Completely Randomized Design (CRD) with factorial arrangements with three replications. First factor used in the experiment was the duration of concentrate feeding (15 days, 30 days, 45 days and 60 days) and second was amount of concentrate supplemented (2.00%, 1.75%, 1.50% and 1.25% of their body weight). Birth weight, weaning weight, milk yield and kid mortality in different groups were recorded. Birth weight and weaning weight were found higher in 60 days supplemented group i.e. 2.3±0.23 kg and 10.94±0.41 kg, respectively. Both birth weight and weaning weight were also found higher with 2 percent concentrate feeding group than others i.e. 2.1±0.23 kg and 9.64±0.42 kg, respectively. Milk yield recorded for fourth week shows that higher milk yields were found in 2 percent concentrate supplemented group with 60 days time period. The result showed that by increasing the level of concentrate during late gestation period of does increased the birth weight, weaning weight of kids and increased milk yield of does. So the higher level of concentrate supplementation is required during 45 to 60 days of late gestation in does. Bang. J. Anim. Sci. 2019. 48 (1): 57-66